X-ray crystallographic and validated HPTLC analysis of the biomarker chromone glucoside (schumanniofioside A) isolated from Acalypha fruticosa growing in Saudi Arabia - Areej M. Al-Taweel; Ghada A. Fawzy; Shagufta Perveen; Perwez Alam; Ali A. El Gamal (Elsevier, 2017)
A chromone glucoside 2-methyl-5,7-dihydroxychromone 5-O-β-D-glucopyranoside (schumanniofioside A, compound 1) was isolated from the methanol extract of Acalypha fruticosa. The structure of compound 1 was fully assigned based on nuclear magnetic resonance (NMR) (1H, 13C and 2D) spectra and electrospray ionization mass spectrum (ESI-MS) in addition to X-ray Crystallography. The molecules were packed in the crystal structure by eight intermolecular OH⋯O and CH⋯O interactions. The structure of compound 1 belongs to monoclinic, P21, a = 9.1989 (4) Å, b = 4.6651 (2) Å, c = 20.4042 (7) Å, β = 97.862 (3)°, V = 867.31 (6) Å3, Z = 2, wRref (F2) = 0.101, T = 100 K. Thus, the bond angles, bond lengths and absolute structure of compound 1 were confirmed by its X-ray structure. A validated HPTLC method was developed for the quantitative analysis of compound 1 in chloroform and methanol extracts of A. fruticosa. It was found to furnish a compact and sharp band of compound 1 at Rf = 0.13 ± 0.005 using chloroform, methanol and glacial acetic acid [17:3:0.5 (v/v/v)] as mobile phase. The LOD and LOQ for compound 1 were found to be 17.86 and 54.13 ng/band, respectively. Compound 1 was found in both chloroform and methanol extracts of the plant (0.03% w/w and 0.31% w/w, respectively). The proposed HPTLC method can be used for the further analysis of schumanniofioside A in different plant extracts, herbal formulations and biological samples as well as in process quality control.